VULNERABILITY ANALYSIS FOR EVACUATION TRANSPORTATION NETWORKS - Kim, Jun; Lee, Jae-Hoon; Kim, Hyun-Jung; Chung, Byung Do (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
As occurrences of natural disasters are increasing, interests of reacting for the certain circumstances such as evacuation planning have been rising. When an evacuation network is built, strategic analyses to support operation of the network are needed. Vulnerability analysis that seeks for weak points of an evacuation transportation network is one of those. This paper aims to analyze vulnerability of evacuation transportation network constructed with the Cell Transmission Model (CTM). Previous researches have considered all the possible scenarios to investigate weak points without any mathematical approaches. Accordingly, we propose a bi-level optimization model to identify fragile spots of the network. Due to a complexity of the problem, genetic algorithm combined with a linear programming is developed to find good solutions in reasonable computational time. Solutions from the proposed algorithm are compared with optimal solutions.